Unanticipated Effects of California's Paid Family Leave Program - Tirthatanmoy Das; Solomon Polachek (Institute for the Study of Labor (IZA), 2014)
We examine the effect of California Paid Family Leave (CPFL) on young women's (less than 42 years of age) labor force participation and unemployment. CPFL enables workers to take at most six weeks of paid leave over a 12 month period in order to bond with new born or adopted children, or to care for sick family members or ailing parents. The policy benefits women, especially young women, since they are more prone to take such a leave. However, the effect of the policy on labor market outcomes is less clear. We apply difference-in-difference techniques to identify the effects of the CPFL legislation on young women's labor force participation and unemployment. We find that the labor force participation rate, the unemployment rate, and the duration of unemployment among young women rose in California compared to states that did not adopt paid family leave. The latter two findings regarding higher young women's unemployment and unemployment duration are unanticipated effects of the CPFL program. We utilize a unique placebo test to validate the robustness of these results.
Keywords: H43; J13; J18; J48; 330; paid family leave; maternity leave; unemployment; policy evaluation